2022
DOI: 10.1097/corr.0000000000002466
|View full text |Cite
|
Sign up to set email alerts
|

The Choice of Antibiotic Prophylaxis Influences the Infection Reoperation Rate in Primary Shoulder Arthroplasty: Analysis From the Swedish Shoulder Arthroplasty Register

Abstract: Background Periprosthetic joint infection is a serious complication and a major reason for revision surgery after primary shoulder arthroplasty. The prophylactic antibiotics for primary shoulder arthroplasty that have predominantly been used in Sweden are cloxacillin and clindamycin. To address Cutibacterium acnes, benzylpenicillin has recently increasingly been added to cloxacillin, but it is unclear which antibiotic prophylaxis regimen is the most effective to prevent periprosthetic joint infection. Question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Since C. acnes is an important etiological agent in shoulder PJIs, benzylpenicillin has increasingly been added to routine prophylaxis with cloxacillin for shoulder prosthetic surgery in Sweden. A register-based study [ 33 ] using data from the Swedish Shoulder Arthroplasty Register found that cloxacillin prophylaxis was associated with a significantly increased relative risk of reoperation for infection compared to the combination of cloxacillin and benzylpenicillin. In addition, since cloxacillin has a short half-life, is highly protein-bound, and the free concentration could be affected by the patient’s BMI, serum albumin, and renal function, it may constitute a risk of subtherapeutic concentrations of cloxacillin during surgery in specific patients.…”
Section: Discussionmentioning
confidence: 99%
“…Since C. acnes is an important etiological agent in shoulder PJIs, benzylpenicillin has increasingly been added to routine prophylaxis with cloxacillin for shoulder prosthetic surgery in Sweden. A register-based study [ 33 ] using data from the Swedish Shoulder Arthroplasty Register found that cloxacillin prophylaxis was associated with a significantly increased relative risk of reoperation for infection compared to the combination of cloxacillin and benzylpenicillin. In addition, since cloxacillin has a short half-life, is highly protein-bound, and the free concentration could be affected by the patient’s BMI, serum albumin, and renal function, it may constitute a risk of subtherapeutic concentrations of cloxacillin during surgery in specific patients.…”
Section: Discussionmentioning
confidence: 99%
“…This study from across Sweden reviewed over 10,000 primary shoulder arthroplasties sourced from patients operated on over seven years, including hemiarthroplasties and anatomical and reverse shoulder arthroplasties, via the Swedish Shoulder Arthroplasty Register. 2 Postoperative infection rates were compared using revision for infection as a surrogate marker, and baseline differences were adjusted for variables such as age, sex, previous surgery, cement fixation, and arthroplasty type. The authors analyzed the association between antibiotic prophylaxis regimens (cloxacillin, clindamycin, or a combination of cloxacillin and benzylpenicillin) and the risk of reoperation for infection.…”
Section: Does the Choice Of Antibiotic Prophylaxis Influence Reoperat...mentioning
confidence: 99%